The incidence of benign and malignant tumors among adults with long-term physical disabilities - S. Alekova Todorova (Medičnì Perspektivi)
People with long-term physical disabilities also suffer from different types and nature of tumors as well as general population. Unfortunately, the information about the frequency of these diseases among the specified contingent is very deficient. The objectives of the study were to determine the incidence of benign and malignant neoplasia among the adults and elderly with physical disabilities and to indicate the risk factors for the appearance and development of tumors in this population. In this descriptive survey, 186 people, living in the largest home on the Balkan Peninsula for adults and elderly people with long-term physical disabilities were studied in 2021. 82.79% of the residents were over 51 years of age and almost all of them are inhabited by two residents. 42.47% of the respondents were men and 57.52% – women. Data on the demographic characteristics of the respondents, including their personal lifestyle and self-reported diagnosis of presence and/or history of a tumor formation, were collected through a semi-structured interview. The verification of the collected information about the incidence of benign and malignant lesions among adults with physical disabilities was carried out by means of the application of the second research method – content analysis based on the medical records. For processing and analysis of the collected data, it was used statistical software – IBM SPSS Statistics V21.0. The results showed a significantly high rate in the prevalence of tumor formations in the sample – 24.19%. The pre-cancerous formations have the highest incidence among residents – 42.22% with the most common variant – chronic form of cholecystitis combined with cholelithiasis (37.77%). Prostatic hyperplasia and uterine leiomyoma are the leading benign lesions in male residents – 11.11%, in female respondents – 11.11% respectively. The predominant form of cancer is breast carcinoma – 8.88%. The research found a high prevalence of tumor formations among adult patients with long-term physical disabilities. The harmful impact of a number of behavioral habits and health determinants significantly contributes to this negative tendency.